Financial shocks and their impacts on the banking sector’s clientele in South-East Europe - Kazinczy, Eszter (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2018)
Generally speaking, the banking sector in South-East Europe (SEE) is lagging behind the new member states of the EU both horizontally and vertically. It is characterised by a high level of euro usage, a moderate development process and a general lack of trust. The paper focuses on the general importance of financial development, inclusion and literacy. The analysis highlights theroots  of certain characteristics that are related to financial literacy or behaviour in SEE, by focusing on the shocks that affected the retail segment’s deposits. Based on the relevant literature, the paper finds a list of various shock events from the socialist time period until the 2008 financial crisis that had fundamental affects on the region’s financial habits. Related to this topic, policymakers should address a number of challenges for further stability.